Faktor-faktor yang Mempengaruhi Pola Pangan Harapan (Pph) Di Kabupaten Bandung - Argandi, Syaeful; Trimo, Lucyana; Noor, Trisna Insan (JURNAL AGRIBISNIS TERPADU, 2018)
One way to know food self-sufficiency through the quality of food consumption diversity as measured by Food Harvest Scale (PPH) scores, hereinafter abbreviated as PPH. PPH can be used as a measure of nutritional balance and food diversity consumed by residents in a region. The maximum PPH score, 100 indicates the diverse food consumption situation and both the composition and quality of nutrition (Baliwati, 2011). In practice, the achievement of food quality and quantity indicator in Bandung Regency has not been achieved. This study aims to determine the size of family, education level, and income level of PPH in Bandung regency. The basic method of this research is the explanatory method (Eksplanatory Research). The determination of Paseh and Pasirjambu sub-districts was conducted by purposive sampling, which is determined by the highest and lowest kecamatan PPH. Furthermore the size of respondents using Slovin techniques. To know the factors that influence the PPH in Bandung regency using multiple regression analysis technique and the test is done by using SPSS 20 program. The result of the research shows that the family size, education level and income level have positive influence on PPH Kabupaten Bandung. This means that the higher the size of the family, the level of education and income level then the higher the PPH in Bandung regency.Ã‚Â Keywords: Family size, education level, income level, Food Pattern of Hope (PPH)